2021
DOI: 10.1111/ene.15213
|View full text |Cite
|
Sign up to set email alerts
|

Potential biomarkers identified by tandem mass tags based quantitative proteomics for diagnosis and classification of Guillain–Barré syndrome

Abstract: Background and purpose: Guillain-Barré syndrome (GBS) is an acute inflammatory autoimmune and demyelinating disease of the peripheral nervous system. Currently, valid biomarkers are unavailable for the diagnosis of GBS.Methods: A comparative proteomics analysis was performed on the cerebrospinal fluid (CSF) from 10 patients with GBS and 10 patients with noninflammatory neurological disease (NND) using the tandem mass tags technique. The differentially expressed proteins were analyzed by bioinformatics, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…In a previous study, significantly higher levels of APOC3 were detected in the CSF and serum of GBS patients compared to other neurological diseases and healthy control groups (5). Similarly, current analysis revealed elevated expression of APOC3 in severe GBS cases and GBS patients with positive CSF neurovirus IgG.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…In a previous study, significantly higher levels of APOC3 were detected in the CSF and serum of GBS patients compared to other neurological diseases and healthy control groups (5). Similarly, current analysis revealed elevated expression of APOC3 in severe GBS cases and GBS patients with positive CSF neurovirus IgG.…”
supporting
confidence: 69%
“…In our previous study investigating proteomic differences between the cerebrospinal fluid (CSF) samples of GBS patients and the control group, we observed that the identified proteins were primarily enriched in pathways associated with lipid metabolism (5). Additionally, our study revealed significantly higher expression of APOC3 in the CSF and serum of GBS patients compared to other neurological disease groups and healthy individuals undergoing physical examination (5). A recent investigation demonstrated that APOC3 induces the activation of the NLRP3 through Caspase8 and TLR2/4, leading to the release of interleukins and amplification of the inflammatory response (6).…”
Section: Introductionmentioning
confidence: 99%
“…It is of great importance to explore the risk factors for GBS disease and severe GBS. In our previous study on the proteomics differences between the CSF samples of GBS patients and the control group, it was found that the differential proteins were mainly enriched in lipid metabolism-related pathways ( 5 ). In this study, we explored the potential risk factors for GBS and severe GBS, taking serum lipid factors into account.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies on the clinical epidemiology of GBS, but its cause is not completely clear. A proteomics study of the cerebrospinal fluid of GBS patients showed that the differentially expressed proteins between the GBS and control groups were mainly enriched in pathways closely related to lipid metabolism ( 5 ). It is interesting that the concept of cholesterol toxicity was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…There are several emerging links between APOC3 and inflammation, some of which are associated with APOC3’s regulation of triglycerides and cholesterol and others that are not. Serum APOC3 levels can be elevated in states of inflammation, including the autoinflammatory conditions rheumatoid arthritis ( 62 ), systemic lupus erythematosus ( 63 ), and Guillain-Barré syndrome ( 64 ). In one study, patients with high APOC3 levels undergoing coronary angiography had significantly higher markers of systemic inflammation, such as high-sensitivity C-reactive protein (hsCRP) ( 65 ).…”
Section: Apoc3 Forms and Inflammationmentioning
confidence: 99%